Extra-Cavity Modulating a Soliton Molecule with Chirped Gaussian Pulse Shape - Daqian Tang; Junxiao Zhan; Dayu Wang; Haoming Wang; Yangyang Peng; Zian Cheak Tiu; Yan Zhou (Photonics)
In this work, we theoretically simulate the modulation of a soliton molecule that has an initial chirped Gaussian pulse shape in a 1 μm extra-cavity optical fiber modulation system. Different soliton parameters in orthogonal polarizations are applied to achieve controllable optical solitons’ output with specific properties in the time/frequency domain. For instance, when the phase difference is changed, both pulse shapes’ and corresponding optical spectra’s peak intensities will have a sudden change when the orthogonal phase difference is π/2. These simulation results provide a beneficial reference value for extra-cavity shaping of different solitons that come from nonlinear optical systems. Optimally, the reported results could pave the groundwork for industrial growth in ultrafast laser design.